2018
DOI: 10.1088/1361-6641/aabb8f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of breakdown voltage for fully-vertical GaN-on-Si p-n diode by using strained layer superlattice as drift layer

Abstract: We have demonstrated a vertical GaN-on-Si p-n diode with breakdown voltage (BV) as high as 839 V by using a low Si-doped strained layer superlattice (SLS). The p-n vertical diode fabricated by using the n − -SLS layer as a part of the drift layer showed a remarkable enhancement in BV, when compared with the conventional n − -GaN drift layer of similar thickness. The vertical GaN-on-Si p-n diodes with 2.3 μm-thick n − -GaN drift layer and 3.0 μmthick n − -SLS layer exhibited a differential on-resistance of 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…By using AlN/GaN SL thin films, Feltin et al, showed a reduction in the tensile stress without getting cracks [17]. Mase et al, improved the breakdown voltage in Si-doped AlN/GaN SL p-n diode [18]. In particular, SL structure could play a significant role in stress management, which reduces GaN tensile stress by providing compressive stress as GaN HEMT heterostructure grown on a silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…By using AlN/GaN SL thin films, Feltin et al, showed a reduction in the tensile stress without getting cracks [17]. Mase et al, improved the breakdown voltage in Si-doped AlN/GaN SL p-n diode [18]. In particular, SL structure could play a significant role in stress management, which reduces GaN tensile stress by providing compressive stress as GaN HEMT heterostructure grown on a silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…But such techniques make the fabrication process more complicated and increase the production cost [11]. Recently, our research group reported the reduction of the series resistance for a fully‐vertical GaN p – n diode on Si without QVS and SRT by introducing a heavily Si‐doped 3‐nm‐thin AlN initial layer on Si followed by a 3.3 μm Si‐doped GaN/AlN SLS structure [12]. Therefore, such an epi‐layer structure could be implemented to improve the current conduction in a fully‐vertical GaN metal‐oxide‐semiconductor field effect transistor (MOSFET) on Si.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to develop a convenient and process compatible device structure, we have implemented a highly doped conductive buffer layer in GaNon-Si epi-structure for the vertical GaN devices. Recently, our research group has demonstrated a method to improve the forward resistance by inserting a heavily Si-doped ultra-thin AlN initial layer on Si and a 3.3 μm-thick conductive n + -GaN/AlN strained layer superlattice (SLS) structure in a fully-vertical structure of a GaN p-n diode on Si [19,20]. A similar buffer layer structure was also employed to develop the GaN-based fully-vertical metal-oxide-semiconductor field-effect transistors (V-MOSFETs) on Si to investigate primitive electrical characteristics of the devices [21].…”
Section: Introductionmentioning
confidence: 99%